Analisis Nilai-Nilai Pancasila dalam Makna Kebudayaan Tarian Tebe Di Desa Tohe Leten Kabupaten Belu Provinsi Nusa Tenggara Timur - Ikhwaningrum, Dian Utami; Loko, Maria Matilde (FKIP Universitas Wisnuwardhana, 2021)
Indonesia is a country that has a wide variety of cultures and national wealth which must be used as one of the nation's identities which can bring about change in Indonesia culturally and openness in the attitude of society which encourages the progress of the nation, all because of the Indonesian philosophy called Pancasila. One of the typical dances of the people of Tohe Leten and Raihat subdistrict in East Nusa Tenggara (NTT) is the tebe dance. The Tebe dance is performed by men and women holding hands while singing in unison, chanting poetry and rhymes containing praise, criticism, or requests, while stomping their feet to the rhythm of the song. However, many of the younger generation of the Tohe Laten community cannot yet do the tebe dance and the meaning of each movement in the tebe dance. The purpose of this research is (1) to find out how the study of tebe dance in Tohe Leten village is conducted (2) to find out the Pancasila values ??contained in the meaning of tebe dance in Tohe Leten village (3) to find out how the community preserves tebe dance in Tohe village leten. Based on the research results, the cultural meaning of tebe dance in Tohe Leten village is the first study of tebe dance in Tohe Leten village, which is an expression of joy at success on the battlefield against the Dutch. Tebe dance is a dance that originates from Tohe Leten village, Raihat subdistrict, East Nusa Tenggara which was born around 1990. Meanwhile, the Pancasila values ??contained in the Pancasila cultural meaning are the values ??of leadership, human values, unity values, populist values??, and justice values. The community preserves this tebe dance by holding competitions and traditional events.